2022
DOI: 10.1093/jscr/rjac026
|View full text |Cite
|
Sign up to set email alerts
|

Liver abscess secondary to fishbone ingestion: case report and review of the literature

Abstract: We report a rare silent migration of a fishbone into the liver and review the relevant literature. A 56-year-old man presented with a 2-day history of dull epigastric pain and raised inflammatory markers. Computerized tomography scan revealed a 4-cm abscess in the left lobe of the liver, with a linear radio-dense foreign body within the collection. At laparoscopy the hepatogastric fistula was disconnected. The fishbone was retrieved from the liver. Gastrostomy was closed with an omental patch. The patient had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Various kinds of objects can be swallowed intentionally or more frequent accidently. However, sharp, indigestible ones tend to cause damage, for example, fishbones [8] , [9] , chicken bones [1] , sewing needles, and toothpicks. All people may swallow FBs by accident.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various kinds of objects can be swallowed intentionally or more frequent accidently. However, sharp, indigestible ones tend to cause damage, for example, fishbones [8] , [9] , chicken bones [1] , sewing needles, and toothpicks. All people may swallow FBs by accident.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical manifestations are contingent on many factors such as the time, site and depth of the perforation. The most frequent symptoms related to liver abscess induced by a foreign body are pain [9] , [12] , [14] and fever [16] . In contrast, migration of foreign bodies can stay silent until manifested as an abscess or an accidental finding, as what Al-Khyatt et al have reported; a toothpick was found accidentally in the porta hepatic during laparoscopic cholecystectomy [12] .…”
Section: Discussionmentioning
confidence: 99%
“…Of the 12 cases (44%) with symptoms such as abdominal pain, 5 (19%) had liver abscesses. Fish bones are often detected as liver abscesses [ 5 ], whereas sewing needles are characterized by the fact that several patients are asymptomatic. In the case of sewing needles, asymptomatic patients can be followed up with the appearance of symptoms, such as abdominal pain and fever, and with imaging studies.…”
Section: Discussionmentioning
confidence: 99%
“…The key aspects of treatment for hepatic abscesses caused by foreign body-induced GI perforation is early diagnosis and prompt removal of the foreign body[ 2 , 10 ]. Simple percutaneous drainage of the abscess may transiently alleviate symptoms; however, recurrent episodes of sepsis might follow and surgical removal of the foreign body is likely to be required in the end[ 12 ]. The removal of foreign bodies from the liver can be performed by endoscopic procedures, laparoscopic surgery, or open surgery[ 13 ].…”
Section: Discussionmentioning
confidence: 99%